Metastatic melanoma response to combination therapy with ipilimumab and vemurafenib - Sachpekidis, Christos; Hassel, Jessica C.; Dimitrakopoulou-Strauss, Antonia (Hellenic journal of nuclear medicine, 2017)
Combination therapies for the treatment of metastatic melanoma are a matter of debate nowadays. We report on a stage IV metastatic melanoma patient with the BRAF V600 mutation and a large tumor burden initially treated with two cycles of ipilimumab. Due to dramatic disease progression, demonstrated on interim 18F-FDG PET/CT, vemurafenib was added in the patients therapeutical scheme. After completion of the concurrent ipilimumab and vemurafenib administration, a third 18F-FDG PET/CT showed an impressive metabolic remission of the metastatic disease, reflecting the potential role of the modality in treatment response evaluation of melanoma patients receiving combination therapies.